Novel Quantitative Method for Assessing Driving Forces of Landscape Succession: Case Study From Yancheng Coast, China - Wang, Zhi; Xu, Wanggu; Xia, Xin; Yu, Huanxi; Lv, Yingying; Zhang, Jianliang (Frontiers in Ecology and Evolution, 2021)
Variation of landscape pattern can provide key information of human activity effects on landscape and consequently has received much attention in recent years. The paper mainly deals with the Spatio-temporal variation and driving force of the landscape pattern in Yancheng coast with remote sensing and GIS employed. The results indicate: (1) The major landscape has always been farmland from 1984 to 2008, not wetland. The landscape matrix had changed, which from the situation that natural landscape was equal with artificial landscape in 1984 to just the latter was dominant during 1990-2008. The proportion of natural landscape is 51.07% in 1984, and its proportion is 28.82% in 2008. (2) The area of natural landscape decreased remarkable, which includes reed fields, Suaeda salsa fields, and mudflats. The area of Spartina alterniflora fields (alien invasive species) and artificial landscape increased significant. The majority of increased artificial landscape are farmland and aquaculture ponds. (3) The change of these landscapes showed a regular pattern, from natural landscape to artificial landscape. (4) According to analysis the transition rate of landscape in Yancheng coast during each phase, we concluded that the main driving force of coastal landscape pattern change is land use by human. It provides a new quantitative way to assess driving forces of landscape patterns change.